Entrepreneurship in a global context - Birley, Sue; MacMillan, Ian C., 1940- (Routledge, 1997)
This collection presents selected papers from the Fourth Annual Global Conference on Entrepreneurial Research, held in 1994 at INSEAD, France.
Selected papers from the Fourth Annual Global Conference on Entrepreneurship Research, held in 1994 at INSEAD, France.
Keywords: International business enterprises -- Management -- Congresses.; Entrepreneurship -- Congresses.; Entreprises multinationales -- Gestion -- Congrès.; Entrepreneuriat -- Congrès.; BUSINESS & ECONOMICS -- Entrepreneurship.; Entrepreneurship; International business enterprises -- Management; Ondernemingsgeest.; Internationalisatie.; Ondernemerschap.; Electronic books.; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings.; Actes de congrès.